Teaching the alphabetic code from the phonological path - Mena, Soledad (2020)
When a person is learning the phoneme-grapheme relationship, s/he is not learning to read or write; s/he is learning the alphabetic code. Learning the alphabetic code is valued by teachers, which is why this proposal is constructed as an alternative to nonsense teaching of the syllabic method. This proposal takes advantage of the characteristic of transparency that the Spanish language has. This proposal guides the students to manipulate the phonemes that make up the words to propose graphing hypotheses through the development of phonological awareness. This device is an alternative for the mechanical and associationist teaching of the alphabetic code.